Nonstandard Interactions and Prospects for Studying Standard Parameter Degeneracies in DUNE and T2HKK - Surender Verma; Shankita Bhardwaj (Advances in High Energy Physics)
The future long baseline experiments such as DUNE and T2HKK have promising prospects to determine the neutrino mass hierarchy and measuring standard CP phase δ. However, presence of possible nonstandard interactions of neutrinos with matter may intricate this picture and is the subject matter of the present work. We have studied the standard parameter degeneracies in presence of nonstandard interactions (NSI) with DUNE and T2HKK experiments. We examine the mass hierarchy degeneracy assuming (i) all NSI parameters to be nonzero and (ii) one NSI parameter (ϵeμ) and its corresponding CP phase (δeμ) to be nonzero. We find that the latter case is more appropriate to resolve mass hierarchy degeneracy with DUNE and T2HKK experiments due to relatively small uncertainties emanating from the NSI sector. We have, also, investigated the octant degeneracy with neutrino (νμ→νe) and antineutrino (ν¯μ→ν¯e) mode separately. We find that to resolve this degeneracy the long baseline experiment with combination of neutrino and antineutrino mode is essential. Furthermore, we have considered DUNE in conjunction with T2HKK experiment to study CP phase degeneracy due to standard (δ) and nonstandard (δeμ) CP phases. We find that DUNE and T2HKK, in conjunction, have more sensitivity for CP violation effects (10σ for true NH and 8.2σ for true IH).